International Alliance of Urolithiasis (IAU) guideline on staghorn calculi management - Zhong, Wen; Osther, Palle; Pearle, Margaret; Choong, Simon; Mazzon, Giorgio; Zhu, Wei; Zhao, Zhijian; Gutierrez, Jorge; Smith, Daron; Moussa, Mohamad; Pal, Shashi Kiran; Saltirov, Iliya; et al. (World journal of urology, 2024)
Background: The stone burden based management strategy reported in the guidelines published by different associations is well known for a long time. Staghorn calculi, representing the largest burden and most complex stones, is one of the most challenging cases to practicing urologists in clinical practice. The International Alliance of Urolithiasis (IAU) has released a series of guidelines on the management of urolithiasis.Purpose: To develop a series of recommendations for the contemporary management management of staghorn calculi and to provide a clinical framework for urologists treating patients with these complex stones.Methods: A comprehensive literature search for articles published in English between 01/01/1976 and 31/12/2022 in the PubMed, OVID, Embase and Medline database is performed. A series of recommendations are developed and individually graded following the review of literature and panel discussion. Results: The definition, pathogenesis, pathophysiology, preoperative evaluation, intraoperative treatment strategies and procedural advice, early postoperative management, follow up and prevention of stone recurrence are summarized in the present document. Conclusion: A series of recommendations regarding the management of staghorn calculi, along with related commentary and supporting documentation offered in the present guideline is intended to provide a clinical framework for the practicing urologists in the management of staghorn calculi.